MODELING OF REACTIVATION PROCESS OF CR-MN OXIDE SYSTEMS IN ORDER TO IMPROVE THE EFFICIENCY OF DIRECT ALLOYING OF IRON-CARBON ALLOYS - G. V. Jandieri; I. S. Dzhanelidze; E. S. Dzhanelidze (Литьë и металлургия)
Questions of the improvementof the efficiency of technology direct doping of steel and alloys by thermodynamic modeling of recovery of target metals from complex oxide system Cr2O3-MnO-SiO2are shown.